Estimation of grain sorgo development under phenological observations - Свиридова, Л. А.; Рожков, А. О. (Scientific Progress & Innovations, 2017)
The results of the four-year research concerning the influence of technological factors dealing with the: methods of sowing and seeding standards during the individual certain stages of the grain sorghum plants development are presented. The experiments proved the influence of these factors on the variability of the duration of the studied phases concerning growth and development of plants. When the coenotic stress in the crops grows weak due to the use of a broad-row sowing method with intermediate rows of 45 cm and seeding standards of 120 and 160 thousand pcs./ha, the accelerated tubing phase passage of grain sorghum crop was noted. At the same time, when the competition in plant crops to optimize the sowing method and reduce the seed rate became low on the contrary, it caused the «stretching» of the busing phase and the interphasal period of grain forming and ripening, which contributed to a more complete use of agrarian resources and the formation of higher crop yields. The marked patterns were manifested during all years of research.